Service Use, Drop-Out Rate and Clinical Outcomes: A Comparison Between High and Low Intensity Treatments in an IAPT Service - Chan, Stella W. Y.; Adams, Malcolm (Behavioural and cognitive psychotherapy, 2014)
Background: The IAPT services provide high and low intensity psychological treatments for adults suffering from depression and anxiety disorders using a stepped care model. The latest national evaluation study reported an average recovery rate of 42%. However, this figure varied widely between services, with better outcomes associated with higher “step-up” rates between low and high intensity treatments. Aims: This study aimed to compare the two intensity groups in an IAPT service in Suffolk. Method: This study adopted a between groups design. A sample of 100 service users was randomly selected from the data collected from an IAPT service in Suffolk between May 2008 and February 2011. The treatment outcomes, drop-out rate, and other characteristics were compared between those who received high and low intensity treatments. Results: The high intensity group received, on average, more sessions and contact time. They received more CBT sessions and less guided self-help. There were no group differences in terms of the drop-out and appointment cancellation rates. Analyses on clinical outcomes suggested no group difference but demonstrated an overall recovery rate of 52.6% and significant reduction in both depression and anxiety symptoms. Conclusions: Despite methodological limitations, this study concludes that the service as a whole achieved above-average clinical outcomes. Further research building upon the current study in unpacking the relative strengths and weaknesses for the high and low intensity treatments would be beneficial for service delivery.